A nonlinear stochastic growth model on discrete time domains. Issue 11 (1st November 2016) - Atıcı, Ferhan M.; Cheng, Gang; Lebedinsky, Alex
Abstract : In this paper, we introduce nonlinear stochastic dynamic problems on discrete time domains where events may occur at unevenly spaced time points. We define Euler equation and transversality condition for the problem. We prove that the Euler equation and the transversality condition are sufficient for the existence of the optimal solution. Next we generalize discrete time Cagan type rational expectation model to multivariate case. As an application of the main results, we obtain an explicit solution to a log-linearized nonlinear stochastic growth model.